Effect of Easiness, Service Quality, Price, Trust of Quality of Information, and Brand Image of Consumer Purchase Decision on Shopee Online Purchase - Goldianus Solangius Mbete; Rinabi Tanamal (Teknik Informatika Universitas Pamulang, 2020)
Technological developments are so rapid to bring impact and influence to all areas of life without exception e-commerce. Recent advances in web-based technologies and applications lead to the emergence of new developments that affect electronic trading. Trade of e-commerce encourages consumers to actively participate in the purchase and sale of products and services in the market and online community. However, the effect on the factors that influence and make the consumer are interested of trading the e-commerce marketplace/ platform has not yet achieved the right formula and is not well understood, causing policy-making are less effective in increasing consumer purchase decisions can thus have a negative impact on online purchase behavior of consumers. In this study proposed several variables that are considered influential in the purchase decision of the consumer (such as convenience, quality of service, price, trust, information quality and brand image) that will be modeled in the form of a hypothesis and the next will be in to do testing to prove the hypothesis on the independent variables proposed. The results of the study shows that the ease and brand image have a positive significant impact on purchase decisions online in the marketplace Shopee. While the quality of service, price, trust and information quality has no significant effect on purchasing decisions online in the marketplace Shopee. Shopee can maintain and evaluate the level of convenience and a brand image that is already good and improve the quality of service, price, trust and information quality as an effort to improve the purchase decision of the consumers.